Association of IRGM gene promoter polymorphisms with hepatitis B virus infection. (21st June 2022) - Sharma, Ambika; Duseja, Ajay; Parkash, Jyoti; Changotra, Harish
Abstract: Background: In response to intracellular pathogens, the autophagy gene IRGM plays an essential role in the innate immune response. Various identified IRGM gene risk loci are associated with several diseases but, so far, no study is available that shows the association of IRGM with hepatitis B virus (HBV) infection. Methods: We genotyped promoter variants (rs4958842, rs4958843, and rs4958846) of IRGM in HBV infected patients (551) and healthy controls (247) for their role in HBV infection. The genotyping was performed by applying methods developed in our laboratory and various biochemical parameters were assessed applying commercially available kits. Results: Data analysis has shown that the mutant allele A of rs4958842 plays a role in the protection from HBV infection in various genetic models that includes allelic, co‐dominant and dominant models with the respective statistical data: allelic (odds ratio [OR] = 0.61; 95% confidence interval [CI] = 0.48–0.78; p  = 0.0003), co‐dominant (OR = 0.52; 95% CI = 0.38–0.71; p  = 0.0008) and dominant (OR = 0.51; 95% CI = 0.38–0.70, p  = 0.0004). In chronic hepatitis B (CHB), protective association was observed in the allelic (OR = 0.48; 95% CI = 0.35–0.65, p  = 0.0004), co‐dominant (OR = 0.38; 95% CI = 0.26–0.54, p  = 0.0004) and dominant (OR = 0.38; 95% CI = 0.26–0.54, p  = 0.0002) models. Mutant allele C of rs49598843 was associated with the risk of CHB in co‐dominant (OR = 1.52; 95% CI = 1.07–2.16, p  = 0.04) and dominant (OR = 1.41; 95% CI = 1.00–2.00, p  = 0.04) models. The mutant allele C of rs4958846 decreased the risk of HBV infection in allelic (OR = 0.74; 95% CI = 0.59–0.92, p  = 0.01), dominant (OR = 0.72; 95% CI = 0.53–0.98, p  = 0.05), homozygous (OR = 0.42; 95% CI = 0.24–0.74, p  = 0.01) and recessive (OR = 0.42; 95% CI = 0.24–0.74, p  = 0.0004) models. However, in the asymptomatic group, it was associated with the increased chance of HBV infection. Haplotypes, ATT (OR = 0.47; 95% CI = 0.33–0.68, p  = 0.001) and GTC (OR = 0.68; 95% CI = 0.51–0.92, p  = 0.01) protect, whereas GTT (OR = 2.01; 95% CI = 1.55–2.60, p  < 0.0001) predisposes the individuals to HBV infection. All of these p  values mentioned here were obtained after performing Bonferroni correction. Conclusions: In conclusion, our findings revealed that mutant allele A of rs4958842, mutant allele C of rs4958843 and rs4958846 were associated with hepatitis B virus infection in the North Indian population. Abstract : This case–control study found that mutant alleles A (rs4958842), C (rs49598843) and C (rs4958846) are respectively associated with the protection of HBV infection (allelic, co‐dominant and dominant models), the risk of CHB (co‐dominant) and decreased risk of HBV infection (allelic dominant, homozygous and recessive models).